Judicial denationalisation of Dominicans of Haitian descent - Gamboa, L; Reddy, J (Refugee Studies Centre, University of Oxford, 2014)
A recent Constitutional Tribunal decision in the Dominican Republic, if implemented as drafted, will leave thousands of Dominicans stateless and send a lesson to other states that mass arbitrary denationalisations are acceptable as long as they are judicially mandated